Efektivitas Waktu Injeksi Insulin terhadap Kadar Glukosa Darah 2 Jam Setelah Makan pada Pasien Diabetes Mellitus Tipe 2 - Willady Rasyid; Busjra M Nur; Diana Irawati; Fitrian Rayasari (Jurnal Keperawatan Silampari, 2019)
The aim of the study was to analyze the effectiveness of insulin injection time on blood glucose levels 2 hours after meals. The research design was experimental randomized pretest-posttest two group design. The results of the study, blood glucose levels of intervention I before meals (234.88 mg / dl ± 79.68) and 2 hours after meals (246.94 mg / dl ± 76.76) with a p value of 0,000. Intervention II (234.12 mg / dl ± 80.86), 2 hours after eating (252.35 mg / dl ± 78.79) with a p value of 0,000. Difference in blood glucose levels of intervention I and intervention II (12.06 ± 3.96), (18.24 ± 4.97) with a p value of 0.000. The influence of BMI counfounding variables on blood glucose levels was obtained (p values 0.008 and 0.037). Conclusion, giving insulin injection 0-10 minutes is more effective compared to giving insulin injection 11-20 minutes before meals in patients with type 2 DM. Keywords: Type 2 diabetes, blood glucose 2 hours after meals, insulin injection time